GAMBARAN ARSITEKTUR TIDUR PADA PASIEN TUMOR OTAK YANG MENGALAMI GANGGUAN TIDUR - Yesi Astri; Manfaluthy Hakim; Tiara Aninditha; Renindra Ananda Aman; Astri Budikayanti (NEURONA, 2021)
Introduction: Sleep disorder is commonly found in brain tumor patients (42-46%). It can be detected using thePittsburg Sleep ????uality Inde???? (PS????I) as a screening tool and confirmed by analyzing the sleep architecture obtainedthrough a Polysomnographic (PSG) examination.Aim: To evaluate the sleep architecture in brain tumor patients who experience sleep disorder.Methods: In this descriptive cross-sectional study, patients with primary brain tumor were screened for sleep disorderusing the PSQI. The ‘poor sleepers’ would proceed to PSG examination.Results: Of 40 participants, 14 were males and 26 were females with a mean age of 45.5±11.7 years old. The mostprevalent tumor was meningioma (42.5%), while the most affected regions were the frontal lobe (40%) and the sellarsuprasellarregion (2????.5%). Poor sleep ????uality and difficulty in initiating sleep (????3 times per week) was reported in77.5% and 60% of participants, respectively. All participants experienced reduced sleep duration, the majority of whichdemonstrated low sleep efficiency (8????.5%). An estimate of 60% participants e????perienced headache at night and 50% tooksleeping pills for these complaints. Most of them reported disruption in daytime activities. On PSG analysis, we observedshortening of sleep latency, reduced sleep efficiency, total sleep time, N2, N3, REM, arousal inde????, and increase of N1.There was a statistically significant difference between ????5 hours of sleep duration and decrease of N3 phase (p????0.05).Discussion: Abnormal sleep architecture presents in brain tumor patients with sleep disorder.Keywords: brain tumor, Pittsburgh Sleep Quality Index, polysomnography, sleep architecture